Response of Sorghum to Cold Stress at Early Developmental Stage - Amandin Rutayisire; Geoffrey Lubadde; Alice Mukayiranga; Richard Edema (International Journal of Agronomy)
Native and adapted to the semiarid tropical regions of Africa, sorghum (Sorghum bicolor) is generally sensitive to cold temperatures, especially during the early developmental stages. However, there is genetic variability within the existing germplasm in terms of tolerance to low temperatures. The highland regions of Africa possess important sources of germplasm with adaptation to cold stress, since they tend to be cooler than the low land regions. The goals of the study were to evaluate and identify sorghum lines with tolerance to cold temperature stress and make recommendations on varieties that may be planted in the East African highland regions or used in plant breeding programs for cold tolerance. Forty sorghum genotypes were evaluated for emergence, shoot, and root development at seedling stage under controlled environment in growth chambers and in the field. Significant genotypic differences were detected for all evaluated traits. Correlation between controlled environment experiments and field trial results was mostly significant, suggesting that the growth chambers can be used to predict and identify cold-tolerant genotypes. Results showed that emergence and vigor are the best surrogate traits for selecting cold-tolerant genotypes. Using rank summation index, we were able to identify the best cold-tolerant sorghum genotypes (IS 25557, IS 25558, IS 25546, BM6, BM 29, IESV 90042LT, and Cytanobe) that can be used in future breeding programs and enhance adaptation and expansion of sorghum production further into the highland regions of Africa.